FUZZY CLUSTERING DALAM PENGCLUSTERAN DATA CURAH HUJAN KOTA BENGKULU DENGAN ALGORITMA C-MEANS - Sari, Herlina Latipa (Universitas Bina Darma, 2014)
This study was conducted to design Clustering using Fuzzy C - Means algorithm rainfall data in the city of Bengkulu and evaluate performance C - Means Algorithm to generate the level of location accuracy in forecasting monthly rainfall Climatological Station Island Baai Bengkulu . The analyzed using C - Means algorithm in which the testing is done using matlab software. From the test using a software assisted SOCR test results obtained by using Fuzzy C - Means for clustering data based on the degree of membership that the resulting cluster centers in reaching target function looking for the best location for the clusters can be done faster as indicated by termination of the iteration process. The output of the fuzzy C - Means is not a Fuzzy Inference System , but a row of cluster centers and some degree of membership for each data point.